Plant Uptake of Atmospheric Carbonyl Sulfide in Coast Redwood Forests. Issue 12 (29th December 2017) - Campbell, J. E.; Whelan, M. E.; Berry, J. A.; Hilton, T. W.; Zumkehr, A.; Stinecipher, J.; Lu, Y.; Kornfeld, A.; Seibt, U.; Dawson, T. E.; Montzka, S. A.; Baker, I. T.; et al.
Abstract: The future resilience of coast redwoods ( Sequoia sempervirens ) is now of critical concern due to the detection of a 33% decline in California coastal fog over the 20th century. However, ecosystem‐scale measurements of photosynthesis and stomatal conductance are challenging in coast redwood forests, making it difficult to anticipate the impacts of future changes in fog. To address this methodological problem, we explore coastal variations in atmospheric carbonyl sulfide (COS or OCS), which could potentially be used as a tracer of these ecosystem processes. We conducted atmospheric flask campaigns in coast redwood sites, sampling at surface heights and in the canopy (~70 m), at the University of California Landels‐Hill Big Creek Reserve and Big Basin State Park. We simulated COS atmosphere‐biosphere exchange with a high‐resolution 3‐D model to interpret these data. Flask measurements indicated a persistent daytime drawdown between the coast and the downwind forest (45 ± 6 ppt COS) that is consistent with the expected relationship between COS plant uptake, stomatal conductance, and gross primary production. Other sources and sinks of COS that could introduce noise to the COS tracer technique (soils, anthropogenic activity, nocturnal plant uptake, and surface hydrolysis on leaves) are likely to be small relative to daytime COS plant uptake. These results suggest that COS measurements may be useful for making ecosystem‐scale estimates of carbon, water, and energy exchange in coast redwood forests. Plain Language Summary: The future resilience of coast redwoods ( Sequoia sempervirens ) is now of critical concern due to the detection of a 33% decline in coastal fog that sustains these forests. However, monitoring the potential impacts on redwood forests is challenging because the unique features of the coastal environment interfere with ecological measurement techniques. Here we propose a solution involving a new technique using carbonyl sulfide, an atmospheric chemical that is related to carbon dioxide. We found that the redwoods remove carbonyl sulfide from the atmosphere, which is a critical prerequisite for using this technique to explore redwood resiliency. Key Points: First atmospheric carbonyl sulfide (COS) measurements in a coast redwood forest Measurement shows persistent daytime COS depletion and COS:CO2 linear relationship Results support use of COS as a biogeochemical tracer of photosynthesis